Analisis Pengaruh Company Growth, Investment Opportunity Set, Debt Covenant Dan Corporate Social Responsibility Terhadap Konservatisme Akuntansi Pada Perusahaan Manufaktur Sektor Basic Materials Yang Terdaftar Di Bursa Efek Indonesia Tahun 2020 – 2022 - Salwaa Salsabiil; Murniati (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
Companies listed on the stock exchange must disclose financial reports that can be accessed by the public on the idx.com website. This study aims to assess the effect of company growth, investment opportunity set (IOS), debt covenant, and corporate social responsibility (CSR) on accounting conservatism in manufacturing companies in the basic materials sector listed on the Indonesian stock exchange from 2020 to 2022. Using a quantitative approach, this study uses multiple linear regression analysis to explore the correlation between variables. This study uses secondary data with a total population of 24 companies selected from 96 manufacturing companies in the basic materials sector. The results show that company growth has a significant effect on accounting conservatism, while investment opportunity set (IOS) and debt covenant do not show a significant effect individually. On the other hand, corporate social responsibility (CSR) has a significant impact on accounting conservatism.